Menjelajahi Kemungkinan Transhumanisme Sebagai Imago Dei - Stella Lusiana; Yahya Wijaya (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2025)
This article relates technological developments, specifically artificial intelligence, to the theological concept of Imago Dei. Transhumanism dreams of technological progress that can overcome human biological limitations. The idea has implications for anthropology and theology. Can transhumans replace humans not only biologically but also ethically and spiritually? This question will be answered by borrowing Alistair McFadyen's theory of Imago Dei which understands this theological concept as a call to a participation in God's work that saves and transforms the world. If Imago Dei refers not to the original nature of humans that is fixed from the beginning, but to the possibility of its development in the future, then there is potential for alignment of transhumanism with Imago Dei theology. Moreover, Imago Dei can make an ethical contribution and eschatological vision for the development of human enhancement technology so that it can help to result in the improvement of the common good and the salvation of all creation..